Chapter 7. Cucurbit Production - Craig Frey; Nathan S. Boyd; Qingren Wang; Johan Desaeger; Jawwad Qureshi; Anna Meszaros; Nicholas Dufault; Pamela Roberts; Xavier Martini (EDIS)
Chapter 7 of the Vegetable Production Handbook of Florida